Empirical Studies on Public Debt and Fiscal Transfers - Markus Josef Reischmann (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2016)
This volume includes five self-contained chapters in the fields of public debt and fiscal transfer schemes. After an introduction to the topic, chapter 2 shows that the institutional setting of fiscal policy making needs to be considered when assessing the sustainability of fiscal policy. Using data for the U.S. and German state governments, the results of fiscal sustainability tests depend on whether fiscal transfers are taken into account. If fiscal transfers are not included in the primary surplus, the test results do not indicate that the U.S. and German state governments pursued sustainable fiscal policies. Chapter 3 examines whether the municipalities' voting behavior in state elections in a German state influenced the distribution of discretionary grants from the state level to the municipalities. The results show that discretionary grants were awarded to municipalities with many core supporters of the incumbent state government. In Chapter 4, a test on explosive time-series behavior is applied to the Target balances of the German Bundesbank. Chapter 5 examines whether electoral motives in OECD countries influenced “creative accounting” by the governments as measured by stock-flow adjustments (the difference between budget deficits and the change in public debt). Governments can engage in creative accounting to hide borrowing and sugarcoat the budget balance. The results show that stock-flow adjustments increased before elections. In Germany, stock-flow adjustments chiefly occurred via the creation of off-budget special funds that governments can use to finance public activities outside the core budget. Chapter 6 describes special funds in Germany and elaborates upon the purposes for which special funds were established. It discusses the extent to which the new German debt brake limits the borrowing of special funds and explains how the debt brake can be circumvented by using special funds.
Keywords: C22; C23; D72; E62; H60; H70; P16; 330; Public debt; fiscal sustainability; institutions; fiscal transfers; intergovernmental grants; discretionary grants; fiscal equalization; hidden debt; creative accounting; stockflow adjustments; electoral motives; political business cycles.; Öffentliche Schulden; Neue politische Ökonomie; Finanzausgleich; Parafiskus; Haushaltskonsolidierung; Clearing; Wahlverhalten; Theorie; Schätzung; Deutschland